STRATEGI PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN DANA DESA DI KECAMATAN KABAENA KABUPATEN BOMBANA - Fransin Kontu; Maswar Amdin; Syahrabudin Enala; Novan Prasetya (Nusantara Hasana Journal, 2023)
The strategy of Community Empowerment in Utilization of Village Fund In District Kabaena Bombana Regency. This study aims to: 1) Describe and analyze the community empowerment strategy in utilizing the Village Fund and 2) Describe and analyze the aspects that influence the strategy of empowering the community in the utilization of the Village Fund in District Kabaena Bombana Regency. The Method used in this study using the descriptive qualitative analysis model. To answer the purpose of research involving informants amounted to 11 people consisting of elements of Community Empowerment And Village District Bombana, elements of government District Kabaena, elements of Village Government in Kabaena Subdistrict, and elements of society involved in village fund management in District Kabaena. Determination of Informants in this study using a purposive technique, with the criteria that the selected informant is involved as a member in the Utilization of Village Funds in Kabaena Subdistrict. Conclusion of research: 1) Community empowerment in the utilization of village funds implemented through the planning of program and activity, implementation of an activity that is directly in touch with community requirements, supervision activity of program and activity by giving reports when finding deviations, and empowered in the maintenance of development result related to fulfillment community both physical development in the form of village facilities and infrastructure, social development in the form of training and economic activities of the community supporting the improvement of the village and community progress; 2) Supporting factors for the implementation of community empowerment strategy in the potential and development of the village that is the economic potential of the village, in the form of plantation products, the potential of natural resources in the form of C class mines and the industrial business of the developing community. Regulation or related policy that becomes the legal basis for the development of empowerment strategy either from central government or regional regulation, the social condition of society in the form of education, population and economic condition of society in the form of livelihood, and kind of business that grows in the village, and natural cooperation culture, which is capital in developing community empowerment in the utilization of village funds.